Meta-analysis of the accuracy of CD64, HBP, and PCT in differential diagnosis of sepsis patients - Bin Qiu; Jianjiang Huang; Fang Zhang; Yuyu Wang (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to systematically evaluate the accuracy of the cluster of differentiation 64 (CD64) molecule, heparin binding protein (HBP), and procalcitonin (PCT) in the differential diagnosis of sepsis patients.